Mapping 'New' Geographies of Religion: Politics and Poetics in Modernity - Kong, Lily (Institutional Knowledge at Singapore Management University, 2001)
This article reviews geographical research on religion in the 1990s, and highlights work from neighbouring disciplines where relevant. Contrary to views that the field is incoherent, I suggest that much of the literature pays attention to several key themes, particularly, the politics and poetics of religious place, identity and community. I illustrate the key issues, arguments and conceptualizations in these areas, and suggest various ways forward. These 'new' geographies emphasize different sites of religious practice beyond the 'officially sacred'; different sensuous sacred geographies; different religions in different historical and place-specific contexts; different geographical scales of analysis; different constitutions of population and their experience of and effect on religious place, identity and community; different dialectics (sociospatial, public-private, politics-poetics); and different moralities.